A Novel Single Phase bridgeless AC/DC PFC converter for Low Total Harmonics Distortion and High Power Factor - Santhi Mary Antony; Godwin Immanuel (Institute of Advanced Engineering and Science, 2018)
Now day’s the power factor has become a major problem in power system to improve the power quality of the grid, as power factor is affected on the grid due to the nonlinear loads connected to it. Single phase bridgeless AC/DC power factor correction (PFC) topology to improve the power factor as well as the total harmonic distortion (THD) of the utility grid is proposed. By removing the input bridge in conventional PFC converters, the control circuit is simplified; the total harmonics distortion (THD) and power factor (PF) are improved. The PI controller operates in two loops one is the outer control loop which calculates the reference current through LC filter and signal processing. Inner current loop generates PWM switching signals through the PI controller. The output of the proposed PFC topology is verified for prototype using MATLAB circuit simulations. The experimental system is developed, and the simulation results are obtained.